Aktivitas Pembelajaran Matematika Berbasis Stem Low Cost di Era Pandemi pada Siswa Kelas 2 Sekolah Dasar - Hardani Hardani (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2021)
Mathematics is taught to equip students with the ability in using mathematical knowledge and skills to solve problems in life. The context of learning activities should develop the skills dealing with problem solving. Mathematics learning activities during the pandemic era are often carried out by providing material and discussion of the exercise items both online and offline mode. Learning achievements show that students' critical and creative thinking skills have not developed well. This study is the result of a literature review to examine the LowCost STEM approach in learning in grade 2 elementary schools. The results of the study conclude that Low Cost STEM learning can be carried out with activities both problem-based learning and project-based learning using the five stages of the Engineering Design Process. The final result of the learning is in the form of a bridge rope model product made of paper.